Evidences of Z- and W-Linked Regions on the Genome of Fenneropenaeus chinensis - Wang, Qiong; Lv, Jianjian; Ren, Xianyun; Wang, Jiajia; Jia, Shaoting; He, Yuying; Li, Jian (Frontiers in Marine Science, 2021)
Fenneropenaeus chinensis is a commercially cultured shrimp in China. F. chinensis adults show significant sexual dimorphism, with larger females than males. However, sex determination (SD) of F. chinensis has not yet been elucidated. Clarification of the sex-determining system of F. chinensis could enrich our knowledge of the sex differentiation mechanism in crustaceans and facilitate the study of sex-controlling technologies. Here, we studied the sex-determining system of F. chinensis using the fixation index (FST) between the sexes to detect the genetic differentiation in resequencing data of multiple males and females. We located the candidate sex chromosome in the genome of F. chinensis and concluded the female heterogametic (ZW) SD system. We also assembled female-specific sequences, which could be used as molecular markers to identify the sex of F. chinensis. However, the differentiation of the F. chinensis Z and W chromosome is limited. RNA-seq data detected many genes with male-biased expression in the Z-specific region, which possibly could further intensify the divergency between the Z and W chromosomes.